Color and structure of communication in the architecture of traditional and contemporary Iraqi - Wahed Jassime, Jamal A.; Hussain Jawad, Salam Abdyl; Jaafer, Ali Mohsen (Nahrain University College of Engineering Journal, 2011)
Color is one of the formal construction elements and expressive dimension of the built environment, and is significant through the interaction of a group of actors in the formal construction to him, was reflected in the trends and theories of contemporary architecture. However, the architecture of Iraq have suffered and still suffer from poverty chromatic and clear as a result of lack of familiarity with the science-based accredited in building the color, which called for "clarifying the nature of the actors in the process of building the color of the structure of communication in architecture in general and architecture Iraqi traditional and contemporary, in particular" to represent the research problem. The research aims to "to reveal the actors in the process of building a color as ameans of communication can verify that the privacy of the color composition of Iraq's contemporary architecture." Research was to study aspects of synthetic and analytical to the color as a communication with a view to determining the nature of its structure in architecture Iraqi accordance with the questionnaire prepared for that as a tool for testing, research found to identify the most important elements of building color in architecture traditionalIraqi and how it relates to the specificity determinants of the natural and cultural rights to be taken into account when study of any system for the color of the buildings that can communicate with any orientation of the building within the concept of Iraqi contemporary civilization.